Wayang Existence in The Islamization for Traditional Javanese People - Wijayanti, Kenfitria Diah (el Harakah: Jurnal Budaya Islam, 2019)
Wayang (puppet) is one of Javanese culture form which was originally a cult of the local religion. Wayang has a dimension of spirituality that meets cultural aesthetics. This article focuses on how wayang is used as a preaching medium in the context of the spread of Islam, especially on the Java island and the values of virtue found in wayang stories. This research is a type of library research. The data collection method used is the documentation method. The data in this study is in the form of information on the process of Islamization for traditional Javanese people; the information is from books, literature, journals, and newspapers. Meanwhile, the data analysis technique uses descriptive analysis. Through analysis of the data, the results obtained are: (1) The names of wayang characters contain Islamic philosophical meanings; (2) The wayang stories modified are packed with deep story themes containing Islamic/divine content; (3) The wayang stories had been modified by Walisanga include virtue religious values, leadership values, and human or social values. Wayang merupakan salah satu wujud budaya masyarakat Jawa yang pada mulanya merupakan pemujaan agama lokal. Wayang memiliki dimensi spiritualitas yang bertemu dengan estetika budaya. Artikel ini memfokuskan pada bagaimana wayang digunakan sebagai media dakwah dalam rangka penyebaran agama Islam khususnya di pulau Jawa dan nilai-nilai keutamaan yang terdapat dalam cerita wayang. Penelitian ini merupakan jenis penelitian pustaka. Metode pengumpulan data yang digunakan adalah metode dokumentasi. Data dalam penelitian ini berwujud informasi proses islamisasi masyarakat tradisional Jawa yang berasal dari buku, literatur, jurnal, dan surat kabar. Sementara itu, teknik analisis data menggunakan deskriptif analisis. Melalui analisis data tersebut, diperoleh hasil berupa: (1) Nama-nama tokoh pewayangan mengandung makna filosofis islami; (2) Cerita pewayangan mengalami modifikasi dikemas dengan tema cerita lebet yang memuat konten islami/ketuhanan; (3) Cerita pewayangan yang dimodifikasi para walisanga mengandung nilai keutamaan, yakni: nilai religius, nilai kepemimpinan, dan nilai kemanusiaan atau sosial.